2011
DOI: 10.1143/jjap.50.03cb07
|View full text |Cite
|
Sign up to set email alerts
|

Employ Present Five Masks Amorphous Silicon Thin-Film Transistor Design and Process Flow to Realize 5-in. InGaZnO Active-Matrix Liquid Crystal Display with Improved Stress Stability

Abstract: The present five masks bottom gate and staggered amorphous silicon (a-Si) thin-film transistor (TFT) process flow is not suitable for indium–gallium–zinc-oxide (IGZO) TFT because of its vulnerability to post etching process during the source/drain pattern. Bottom gate and coplanar IGZO TFTs were made feasible through the reverse of second (channel layer) and third (source/drain electrodes) masks process flow to avoid etching damage problem. Besides, the post IGZO nitrous oxygen (N2O) plasma treatment was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[11][12][13] It was also reported that dry etching of S/D electrodes results in a conductive a-IGZO active layer, and a N 2 O plasma treatment before the deposition of a passivation layer can recover the original conductive characteristics of the back-channel surface. 14,15) Ti and Mo have been widely used as S/D electrode materials in a-IGZO TFTs because of their process compatibility with conventional Si-based TFTs. However, to date, there have been few reports on the chemical states at the interfaces and on surfaces composed of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] It was also reported that dry etching of S/D electrodes results in a conductive a-IGZO active layer, and a N 2 O plasma treatment before the deposition of a passivation layer can recover the original conductive characteristics of the back-channel surface. 14,15) Ti and Mo have been widely used as S/D electrode materials in a-IGZO TFTs because of their process compatibility with conventional Si-based TFTs. However, to date, there have been few reports on the chemical states at the interfaces and on surfaces composed of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mobility is not sufficiently high for application in flat panel displays. 3) The obtained low V th and high on/off current ratio could be easily understood using eq. ( 1) because of the use of a high-k material.…”
Section: (B)mentioning
confidence: 94%
“…Zinc oxide (ZnO)-based thin-film transistors (TFTs) have attracted significant attention owing to their high performance and optical transparency in the visible region. [1][2][3][4][5][6][7][8][9][10] However, despite their superior performance, most fabrication methods for the production of ZnO-based thin films involve vacuum processes, such as sputtering, pulsed laser deposition, and plasma-enhanced chemical vapor deposition. [1][2][3][4][5][6][7][8][9][10] Vacuum deposition methods require expensive equipment and result in high manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Due to their superior properties, such as high channel mobilities, low processing temperatures, low off-state leakages, and high optical transparencies, a-IGZO TFTs are considered as the backplane technology for next generation active matrix liquid crystal displays (AMLCDs) and organic light-emitting diode displays (OLEDs). [2][3][4][5][6] In spite of their promising performance, reliability remains a critical issue for a-IGZO TFT technology. These devices could suffer serious performance shift or degradation under bias stress, under illumination, and under environmental aging.…”
Section: Introductionmentioning
confidence: 99%